Bilateral pedaling asymmetry during a simulated 40-km cycling time-trial - Carpes, F. P.; Rossato, M.; Faria, I. E.; Bolli Mota, C. (The Journal of Sports Medicine and Physical Fitness, 2007)
Aim: This study investigated the pedaling asymmetry during a 40-km cycling time-trial (TT). Methods: Six sub-elite competitive male cyclists pedaled a SRM® Training Systems cycle ergometer throughout a simulated 40-km TT. A SRM® scientific crank dynamometer was used to measure the bilateral crank torque (N.m) and pedaling cadence (rpm). All data were analyzed into 4 stages with equal length obtained according to total time. Comparisons between each stage of the 40-km TT were made by an analysis of variance (ANOVA). Dominant (DO) and non-dominant (ND) crank peak torque asymmetry was determined by the equation: asymmetry index (AI%)=[(DO-ND)/DO] 100. Pearson correlation analysis was performed to verify the relationship between exercise intensity, mean and crank peak torque. Results: The crank peak torque was significantly (P<0.05) greater in the 4th stage compared with other stages. During the stages 2 and 3, was observed the AI% of 13.51% and 17.28%, respectively. Exercise intensity (%V.O2max) was greater for stage 4 (P<0.05) and was highly correlated with mean and crank peak torque (r=0.97 and r=0.92, respectively) for each stage. Conclusion: The DO limb was always responsible for the larger crank peak torque. It was concluded that pedaling asymmetry is present during a simulated 40-km TT and an increase on crank torque output and exercise intensity elicits a reduction in pedaling asymmetry.